Angeworben GastarbeiterInnen in Österreich in den 1960er und 1970er Jahren - Lorber, Verena (Transkulturelle Perspektiven, 2017)
***Angaben zur beteiligten Person Lorber: Dr.in Verena Lorber ist Senior Scientist am Fachbereich Geschichte der Universität Salzburg. Zu ihren wissenschaftlichen Schwerpunkten zählen die Historische Migrationsforschung, Oral History, Gender Studies und Regionalgeschichte; The book investigates the labour migration to Austria in the 1960s and 1970s. It focuses on national and international migration politics, economic aspects and regional Developments using the example of Styria, one of the districts of Austria. The research on the living realities of labour migrants from Yugoslavia are an important counter-narrative compared to the state perspective, which is dominated by economic aspects. The aim is to show the complex process of labour migration and the interaction of political, economic, cultural and social aspects of this migration movement